Alignment of non-tax state revenue regulations with sustainable development goals in Indonesia - Firmansyah, Amrie; Wibowo, Puji (WIM Solusi Prima, 2025)
Non-Tax Revenue (PNBP) is a key component of Indonesia's public financial system, supporting government operations and development financing beyond taxation. In line with Indonesia's commitment to the 2030 Sustainable Development Goals (SDGs), this study examines whether the regulatory framework governing PNBP is aligned with the principles of sustainable development. Using a policy content analysis, the study analyzes the normative alignment between PNBP regulations and the SDGs agenda. The research applies a regulatory content analysis approach grounded in public accountability theory. The data consist of laws, government regulations, and ministerial regulations that govern the management of PNBP. The SDGs are used as a normative analytical framework, with a particular focus on SDG 16 (Peace, Justice, and Strong Institutions) and SDG 17 (Partnerships for the Goals), which are most relevant to state revenue governance. The findings indicate that Indonesia's PNBP regulations are normatively aligned with the principles of the SDGs, particularly in terms of institutional strengthening, legal certainty, accountability, and fiscal policy coherence. Nevertheless, this alignment is largely implicit, as sustainable development values are embedded in institutional arrangements and governance norms rather than explicitly stated in regulatory texts. This suggests that PNBP contributes to sustainable development primarily through its governance framework rather than through the direct achievement of sector-specific development targets. The study contributes to the literature on public sector accounting and fiscal policy by providing a normative mapping of the relationship between PNBP regulations and the SDGs, and by offering a conceptual basis for enhancing policy coherence in non-tax state revenue within a sustainable development framework.